Risk Factor in Carcinoma Esophagus in Punjab Region of North India - Mahajan, Divya; Makkar, Nikhil; Singh Banipal, Raja Paramjeet (Asian Pacific Journal of Cancer Biology, 2023)
Background: World over, esophageal cancer is the seventh most common cancer. It accounts for sixth most common deaths related to cancer. Studies have included various risk factors such as tobacco consumption, unhealthy diet like spicy food, alcohol, and diet deficient in trace elements mostly selenium, alkalinity of soil, genetic variation and low socio-economic status, have been implicated in the etiology of esophageal cancer. Method: A descriptive observational study of carcinoma esophagus patients between May, 2019 to October, 2020 was performed. A total of first consecutive 70 patients meeting the eligibility criteria were considered for study. Data was collected by personal interview. Results: Data was collected by personal interview. 82.9% of population resided in rural areas. 100% of patients consumed hot beverages with 70% of patients consumed tea, 11.4% consumed coffee and 18.6% consumed both. 60% of patient population used wood for cooking, 22.9% used liquefied petroleum gas (LPG), and 17.1% used cow dung. 25.7% of population consumed cigarette/Bidi, 10% consumed hookah, 7.1% consumed jarda and 28.6% consumed alcohol. 42.9% of patients had pesticide exposure. 47.6% of squamous cell type had pesticide exposure which was statistically significant. Conclusion: General public should also be made aware of the harmful effects of consuming spicy, high salt diet and hot beverages along with cigarette smoking and alcohol.